Corneal stromal graphite particles after pencil injury - Abdelhalim Atef Algendy; Marwa Farouk Abdelghany (Journal of Clinical Ophthalmology and Research, 2024)
Penetrating ocular injuries from pencils and pencil lead are frequently seen in children and may cause an intraocular infection or serious intraocular sterile inflammatory reaction. However, it has been noted that the carbon particles from pencil lead may remain inert in the eye without inciting inflammation for long duration. We report a case of a 21-year-old male with an intracorneal graphite foreign bodies following penetrating ocular injury.